Hemostats in the clinic - Maithili Joshi; Zongmin Zhao; Samir Mitragotri (Bioengineering & Translational Medicine)
Abstract Given the prevalence of hematological conditions, surgeries, and trauma incidents, hemostats—therapeutics designed to control and arrest bleeding—are an important tool in patient care. The prophylactic and therapeutic use of hemostats markedly enhances survival rates and improves the overall quality of life of patients suffering from these conditions. Since their inception in the 1960s, hemostats have witnessed remarkable progress in terms of the active ingredients utilized, therapeutic outcomes, demonstrated efficacy, and the storage stability. In this review, we provide a comprehensive analysis of commercially available hemostats approved by the FDA, along with newer investigative hemostats currently in active clinical trials. We delve into the modality of active ingredients, route of administration, formulation type, and disease indications of these approved and investigative hemostats. Further, we analyze the trends observed in the hemostat actives for Hemophilia A and B, concluding with insights into the emerging patterns and noteworthy developments to watch for in this dynamic field.